ANALISIS PERBEDAAN KESIAPAN BELAJAR DAN HASIL BELAJAR ANTARA SISWA YANG MENGIKUTI TES OBJEKTIF DENGAN SISWA YANG MENGIKUTI TES ESSAY PADA MATA PELAJARAN PENGANTAR AKUNTANSI DAN KEUANGAN SISWA KELAS X SMK NEGERI BISNIS DAN MANAJEMEN KOTA PADANG - Harmelia, Harmelia (Jurnal Ekobistek, 2017)
This research was aimed at knowing the different analysis of readiness of learning and result of learning student which in objective test with student wich in essay. The type of this research is a comparatif study and the population of the reseach was the students of class X accountancy of SMK Negeri business and managemet padang city amounting to 262student. The sampling technique used was purposive sampling, for class X acountancy SMkN 2, SMKN 3, SMKN 4 Padangwith rule use curriculum 2013 and amount student same. Data were collected by using two different instruments. The first one, a questionaire of readiness. The other one was on objective test of accountancy lesson.The type of data consisted of primary data and secondary data, while the data analysis was descriptive and inductive analysis by using two-ways of ANOVA. The results of the research are (1) result of learning had not significantly by using objective test and essay test (2)there are difference which is signifikant between readiness of learning high lower with result learn which in objective tes and in essay tes. (3) There isinteraction between using readiness of learning and result learn by using objective test and essay test. Keywords: readiness of learning, objective test, essay test, and result learn.